2017
DOI: 10.3892/mco.2017.1125
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of circulating tumor cells in advanced gastric cancer patients receiving chemotherapy

Abstract: Abstract. The identification of circulating tumor cells (CTCs) may provide important prognostic information in several types of solid tumors, including gastric cancer. The aim of this study was to investigate whether CTC count may be used to predict survival in patients with advanced gastric cancer treated with chemotherapy. The CELLection™ Epithelial Enrich kit was used to isolate and purify CTCs from samples of peripheral blood. Immunofluorescent staining was used for CTC counting. High CTC counts were assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 33 publications
(31 reference statements)
0
19
0
Order By: Relevance
“…In recent years, CTCs have emerged as an important tumor biomarker for a wide range of human cancers . Our previous reports of CTC analyses in advanced NSCLC mainly focusing on patients without oncogenic mutations receiving chemotherapy as first‐line treatment demonstrated that CTC counts at baseline and during follow‐up are a strong independent predictor of survival outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, CTCs have emerged as an important tumor biomarker for a wide range of human cancers . Our previous reports of CTC analyses in advanced NSCLC mainly focusing on patients without oncogenic mutations receiving chemotherapy as first‐line treatment demonstrated that CTC counts at baseline and during follow‐up are a strong independent predictor of survival outcomes .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a continuously favorable CTC count or an early shift into a favorable CTC count following therapy could predict an improved prognosis. Similarly, in Liu's report [59], only those patients with a low baseline CTC level or a decreased CTC level after the first cycle of chemotherapy remarkably benefited from the treatment. Those with a baseline CTC level of > 2 cells/5 mL blood, which was determined as an independent poor prognostic marker for PFS and OS, were spared from the adverse reactions of chemotherapy.…”
Section: Ctc Assay For Prognosis and Treatment Management Of Gcmentioning
confidence: 74%
“…[55] The baseline CTC count of >2 cells/5 mL and an increase of the CTC count after the first cycle of chemotherapy was an independent prognostic marker of poor PFS and OS→ patients with a low baseline CTC count or decrease of the CTC count after the first cycle of chemotherapy may benefit significantly from palliative chemotherapy [59] The threshold number of CTCs is significantly associated with different clinical stages and was positively correlated with the value in U/mL of CA724. CTCs technology based on ISET method has a high detection rate.…”
Section: Clinical Implication Of Ctcs In Gcmentioning
confidence: 99%
“…Eighteen of the remaining 21 articles [16, 20, 21, 23, 24, 26, 29, 30, 32-34, 38, 40, 42, 48, 50-52] with 21 arms provided HRs for OS. Nine articles [12,16,20,21,23,24,29,30,40] with 11 arms provided HRs for PFS, and 3 articles [37,39,52] provided HRs for DFS.…”
Section: Study Characteristicsmentioning
confidence: 99%